Evaluation of the Volumizing Performance of a New Volumizer Filler in Volunteers with Age-Related Midfacial Volume Defects - Sparavigna A; La Gatta A; Bellia G; La Penna L; Giori AM; Vecchi G; Tenconi B; Schiraldi C (Dove Medical Press, 2020)
Adele Sparavigna,1 Annalisa La Gatta,2 Gilberto Bellia,3 Laura La Penna,1 Andrea Maria Giori,4 Gabriele Vecchi,4 Beatrice Tenconi,1 Chiara Schiraldi2 1DERMING Srl., Milan, Italy; 2Department of Experimental Medicine, Section of Biotechnology, Medical Histology and Molecular Biology, School of Medicine, University of Campania “L. Vanvitelli”, Naples, Italy; 3Medical Affairs, IBSA Farmaceutici Italia, Lodi, Italy; 4Research and Development, IBSA Farmaceutici Italia, Lodi, ItalyCorrespondence: Adele SparavignaDERMING Srl, Clinical Research and Bioengineering Institute, Via Valassina, 24, Milano, ItalyTel +39 2 2318 3475Email adele.sparavigna@derming.comPurpose: The primary aim of this study was to evaluate the performance of the study product, in terms of volumizing activity as well as the duration of the effect, in women with age-related midfacial volume defects. In addition, the study allowed the evaluation of the tolerability of the product by both volunteers and investigators.Patients and Methods: Twenty-two female volunteers, aged 42– 60 years, participated in this study, which was performed under dermatological control in a single center. After an initial visit at baseline to verify adherence to the protocol criteria, volunteers received an injection of Aliaxin® SV (IBSA Farmaceutici Italia Srl), followed 3– 4 weeks later by a second touch-up treatment to treat eventual asymmetries. Four subsequent visits, the last performed 9 months from the first injection, were performed to evaluate clinically and instrumentally the efficacy of the treatment.Results: Clinical and statistically significant improvement in cheek volume was recorded after the first postinjection visit, and the effect was maintained until the end of the study period. A clinically measurable amelioration of wrinkle severity was also observed. By 3D picture recording and subsequent quantitative analysis, it was possible to determine the efficacy in terms of increased facial volume, which was already appreciable at the first visit, was further increased at the second and third visits and was maintained at the fourth and last visits. The injections were very well tolerated by the volunteers, as determined by their self-evaluation questionnaires.Conclusion: The results of the study confirm the esthetic performance of the study product on age-related midfacial volume defects. The very strong high-volumizing activity of the study product was not only properly determined by the investigators but also confirmed by self-evaluation by the volunteers. These effects were obtained with no appreciable undesired effects.Keywords: midfacial aging, crosslinked hyaluronic acid, clinical assessment, instrumental assessment